Next level screenwriting insights, ideas and inspiration for the intermediate screenwriter - Landau, David 1956-; Carren, David Bennett (Routledge, Taylor & Francis Group, 2019)
"Next Level Screenwriting is an intermediate screenwriting book, for those that have already learned the basics of screenwriting, written a screenplay or two already and want to bring their writing and stories to the next level. Each chapter of the book examines a specific aspect of screenwriting, such as character, dialogue and theme, and then provides the reader with ideas, tips and inspiration to apply to their own writing. Rather than being another "how to" book, this book features a variety of case studies and challenging exercises throughout--derived from a broad selection of successful feature films and TV shows from the 1940s to present day--to help spark the imagination of the writer as they work through different styles and approaches of screenwriting. An absolute must-read for any screenwriter wanting to improve their writing and storytelling skills"--